EFFECT OF META-COGNITIVE STRATEGIES ON THE READING COMPREHENSION SKILLS OF HIGHER SECONDARY SCHOOL STUDENTS IN PAKISTAN - Batool , Memoona; Siddiquah, Aishah (International Journal of Psychosocial Rehabilitation, 2020)
The present study aimed to investigate the effect of metacognitive strategies on the reading comprehension skills of HSSC ESL learners. The literature review revealed a significant relationship between the use of metacognitive strategies and a deeper understanding of reading content. The study reflects whether the use of metacognitive strategies can make learners strategic and critical readers. A pre-post-test experimental design was used. The study included about 70 experimental and 70 control group participants to identify the effect of metacognitive reading strategy training on reading achievement. Reading comprehension texts were used as pre- tests and post-tests. Students’ assignments and answers were analyzed and marked, and a t-test was applied to check how far their reading comprehension skills had improved after using meta-cognitive strategies.